Industrial X-ray film and preparation method thereof
By preparing a silver halide cubic particle emulsion and combining it with in-situ composite modification, the problems of image graininess and silver atom migration in industrial X-ray films were solved, improving image resolution and photosensitivity, while also enhancing film stability.
Patent Information
- Application Number
- CN202511251777.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-12-26
- Estimated Expiration
- 2045-09-03
AI Technical Summary
Existing industrial X-ray films suffer from problems such as noticeable image graininess, lateral migration of silver atoms, and merging of development centers between adjacent grains. Their image resolution and photosensitivity need to be optimized, and their long-term stability is poor.
A metal-organic framework (ZIF-8) was formed by preparing a silver halide cubic particle emulsion and modifying it in situ, adding zinc nitrate aqueous solution and 2-methylimidazole aqueous solution, and then preparing the emulsion layer and coating it using a microgravure coating process.
It improves image resolution and photosensitivity, broadens the photosensitivity range, and enhances the long-term stability of the film, especially its pressure stability and environmental stability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of industrial X-ray film, in particular to an industrial X-ray film and a preparation method thereof. BACKGROUND
[0002] In the field of industrial flaw detection, the main methods currently used include ray flaw detection, ultrasonic flaw detection, magnetic particle flaw detection, eddy current flaw detection and penetration flaw detection. Ray flaw detection is a detection method with a high frequency of use in industrial flaw detection, and its main mechanism is to use the penetration of rays to detect the defects in the interior or surface of a workpiece or a weld, especially the internal structure of a welded part and a steel plate. Industrial flaw detection film is often used in combination with a metal foil (intensifying screen) and irradiation rays to make the photosensitive material photosensitive by absorbing the energy generated by the irradiation of rays on the workpiece, and to form a black silver image after development processing, which is used to find small defects on the workpiece.
[0003] The light source used for industrial non-destructive flaw detection photography is X-ray or γ-ray. X-ray can be generated by an X-ray machine or an X-ray high-energy accelerator, and γ-ray can be generated by a radioactive isotope. X-ray and γ-ray are lights of a certain wavelength, and have strong penetration, with shorter wavelength and stronger penetration.
[0004] In the preparation of industrial flaw detection film, emulsion is usually synthesized by double injection method, neutral method emulsification and the like. In the emulsion of X-ray film, the crystal form of halide silver particles can be cubic particles, potato-shaped particles and T particles, and the average particle size of the particles is generally 0.2-0.6 μm. The emulsion particles are monodisperse and high-resolution emulsion particles, which are conducive to improving the contrast of the film.
[0005] However, the existing industrial X-ray film has obvious granularity of the image in the application process, and has problems of silver atom transverse migration and merging of development centers between adjacent particles, and the image resolution needs to be further optimized. At the same time, the existing industrial X-ray film cannot realize efficient utilization of X-ray photons, and has high critical exposure, and the photosensitive sensitivity and photosensitive response range need to be further optimized.
[0006] Further, the existing industrial X-ray film has poor pressure stability and environmental stability, and is prone to produce fog after being placed and stored in a high temperature and high humidity environment or a pressure environment, and the long-term stability needs to be further improved.
[0007] Based on this, the industrial X-ray film and the preparation method thereof can effectively overcome the problems of obvious image granularity, silver atom transverse migration and merging of developing centers between adjacent particles, improve the image resolution, improve the utilization rate of X-ray photons, effectively improve the photosensitive sensitivity and photosensitive response range, and improve the long-term stability of the industrial X-ray film, in particular, the pressure stability and environmental stability, and have important technical significance and research value. SUMMARY
[0008] To solve the technical problems in the prior art, the application provides a preparation method of an industrial X-ray film, which can effectively overcome the problems of obvious image granularity, silver atom transverse migration and merging of developing centers between adjacent particles, improve the image resolution, improve the utilization rate of X-ray photons, effectively improve the photosensitive sensitivity and photosensitive response range, and improve the long-term stability of the industrial X-ray film, in particular, the pressure stability and environmental stability. The application also provides an industrial X-ray film prepared by the preparation method.
[0009] To solve the above technical problems, the technical scheme adopted by the application is as follows: The preparation method of the industrial X-ray film comprises the following steps: preparing a halogenated silver cubic particle emulsion, in-situ composite modification, preparing an emulsion layer coating liquid, and coating and forming. The method for preparing the halogenated silver cubic particle emulsion comprises the following steps: the photographic gelatin, polyvinylpyrrolidone and sodium dioctyl sulfosuccinate are put into deionized water, uniformly mixed, and then the pH is adjusted to 5.5 and the pAg is adjusted to 7.43; the silver nitrate solution and the potassium bromide solution are added dropwise at the same time under the condition of 55-60 DEG C; after the dropwise addition is completed, the mixture is kept stirring to obtain the halogenated silver cubic particle emulsion. The method for in-situ composite modification comprises the following steps: under the condition of 55-60 DEG C, the pH of the halogenated silver cubic particle emulsion is adjusted to neutral, and the zinc nitrate aqueous solution and the 2-methyl imidazole aqueous solution are added dropwise in sequence; after the dropwise addition is completed, the mixture is kept stirring at 32-35 DEG C to obtain a reaction liquid; the reaction liquid is subjected to ultrafiltration treatment, and the ultrafiltration is performed to 64-67% of the original volume to obtain a modified emulsion of in-situ composite ZIF-8. The modified emulsion is used to prepare the emulsion layer coating liquid, and then the coating and forming are performed to obtain the industrial X-ray film.
[0010] Preferably, in the preparation of the halogenated silver cubic particle emulsion, the weight ratio of the deionized water, the photographic gelatin, the polyvinylpyrrolidone and the sodium dioctyl sulfosuccinate is 950:50-52:4.5-4.8:0.2-0.25. The total volume ratio of the deionized water to the added silver nitrate solution is 1:1.1-1.2. The total volume ratio of deionized water to the added potassium bromide solution is 1:1.1-1.2.
[0011] Preferably, in the preparation of the silver halide cubic particle emulsion, the molecular weight of the polyvinylpyrrolidone is 45000-55000; The concentration of the silver nitrate solution is 2.9-3.1 mol / L, and the concentration of the potassium bromide solution is 2.95-3.15 mol / L.
[0012] Further, in the preparation of the silver halide cubic particle emulsion, at a temperature of 55-60℃, first control the constant dropping rate of the silver nitrate solution and the potassium bromide solution to be 4-4.5 mL / min to perform the first dropping, after the first dropping is completed, heat preservation stirring is performed; then, control the initial dropping rate of the silver nitrate solution and the potassium bromide solution to be 2-2.2 mL / min, the acceleration of the dropping rate is 1.2-1.3 mL / min, and the final dropping rate is 30-32 mL / min to perform the second dropping, after the second dropping is completed, heat preservation stirring is performed, and the silver halide cubic particle emulsion is prepared.
[0013] Preferably, the first dropping time is 5-6 min, and the heat preservation stirring time after the first dropping is completed is 15-20 min; The second dropping time is 50-55 min, and the heat preservation stirring time after the second dropping is completed is 15-25 min.
[0014] Preferably, in the in-situ composite modification, the dropping rate of the zinc nitrate aqueous solution is 1.5-2 mL / min; The dropping rate of the 2-methylimidazole aqueous solution is 0.7-1 mL / min; The heat preservation stirring time at 32-35℃ after the dropping is completed is 3-4 h; The molecular weight cut-off of the ultrafiltration treatment is 50-60 KDa.
[0015] Preferably, in the in-situ composite modification, the concentration of the zinc nitrate aqueous solution is 0.1-0.12 mol / L; The concentration of the 2-methylimidazole aqueous solution is 0.3-0.36 mol / L; The volume ratio of the silver halide cubic particle emulsion, the zinc nitrate hexahydrate aqueous solution, and the 2-methylimidazole aqueous solution is 100:23-25:23-25.
[0016] Further, the method for preparing the emulsion layer coating liquid is that, at a temperature of 45-50℃, the alkylphenol polyoxyethylene ether, the carboxymethyl cellulose, and the neutral silica sol are put into the modified emulsion, after being uniformly mixed, the photographic gelatin is added to adjust the viscosity to 12-18 mpa·s, and the emulsion layer coating liquid is prepared; The weight ratio of the in-situ composite modified emulsion, alkylphenol polyoxyethylene ether, carboxymethyl cellulose, and neutral silica sol is 1000:6-6.5:4-4.3:8-8.5.
[0017] Further, the method for coating and forming is that the emulsion layer coating liquid is coated on the front and back surfaces of the substrate by using a micro-gravure coating process, the single-side coating thickness of the emulsion layer coating liquid is controlled to be 8-10 microns; then the isolation layer coating liquid and the protective layer coating liquid are sequentially coated on the outer surface of the emulsion layer, and the industrial X-ray film is prepared. The isolation layer coating liquid comprises alkylphenol polyoxyethylene ether, glutaraldehyde, deionized water, and gelatin. The protective layer coating liquid comprises alkylphenol polyoxyethylene ether, silicone oil, glutaraldehyde, deionized water, and gelatin.
[0018] An industrial X-ray film is prepared by using the preparation method.
[0019] Compared with the prior art, the industrial X-ray film has the following beneficial effects: (1) In the preparation method of the industrial X-ray film, in the step of preparing the silver halide cubic particle emulsion, polyvinylpyrrolidone and sodium dioctyl sulfosuccinate are used in combination with the double injection process, the spatial steric hindrance effect and the electrostatic stabilization effect of the composite stabilization system composed of polyvinylpyrrolidone and sodium dioctyl sulfosuccinate on the space of the particle preparation material are utilized, the uniform nucleation and controllable growth of the silver halide cubic particles are effectively realized, the silver halide cubic particles with uniform size are prepared, the image granularity is reduced, and the image resolution is improved. In the in-situ composite modification step, zinc nitrate aqueous solution and 2-methylimidazole aqueous solution are sequentially added to the silver halide cubic particle emulsion, ZIF-8 is further compounded on the basis of the silver halide cubic particles by the in-situ composite method, the isolation effect of ZIF-8 on each silver halide cubic particle is utilized, the transverse migration of silver atoms and the combination of developing centers between adjacent particles in the developing process are inhibited, the image edge blurring problem caused by silver diffusion is improved, the image edge sharpness is improved, the image resolution and the photosensitive sensitivity of the industrial X-ray film are further improved, the dynamic range of the industrial X-ray film is widened, and the long-term stability of the industrial X-ray film is improved. The above-mentioned technical means are mutually coordinated and synergized, the problems of obvious image granularity, transverse migration of silver atoms, and combination of developing centers between adjacent particles can be effectively overcome, the image resolution is improved, the utilization rate of X-ray photons is improved, the photosensitive sensitivity and the photosensitive response range are improved, the long-term stability of the industrial X-ray film is improved, and the pressure stability and the environmental stability are improved.
[0020] (2) The equivalent circle diameter of the prepared halogenated silver cubic particles in the preparation of the industrial X-ray film is 0.26-0.30 μm, the size variation coefficient is 7.1-7.6%; the background fog density D0 of the prepared industrial X-ray film is 0.03-0.04, the modulation transfer function MTF 50 is 93-96 lp / mm, the average slope G is 3.7-3.8, the relative sensitivity S is 205-210, the exposure latitude L is 3.5-3.6, the maximum density D max is 5.5-5.6, the contrast coefficient γ is 4.3-4.5, the specific sensitivity S R is 229-233%, and the scratch resistance is 1.20-1.23 N.
[0021] (3) The industrial X-ray film has the following advantages: after being stored for 28 days in a constant temperature and humidity environment with a temperature of 55 ℃ and a relative humidity of 85%, the increment of the background fog density ΔD0 of the film is only 0.03; after being applied with a pressure of 50 N / cm 2 for 6 h, the increment of the background fog density ΔD0 of the film is only 0.02.
[0022] (4) The preparation method of the industrial X-ray film is simple in process and easy to control in preparation process, and is beneficial to large-scale industrial production. DETAILED DESCRIPTION
[0023] In order to have a clearer understanding of the technical features, objects and effects of the present application, the specific embodiments of the present application will be described in detail. It should be pointed out that the following detailed description is exemplary and is intended to provide further description of the present application. Unless otherwise specified, all technical and scientific terms used in the present application have the same meaning as generally understood by those skilled in the art to which the present application belongs.
[0024] It should be noted that the terms used herein are only for the purpose of describing the specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, "first", "second", and the like are used to distinguish similar objects, and are not intended to describe a particular order or sequence, and it should also be understood that when the terms "comprise" and / or "include" are used in the specification, there is a feature, step, operation, device, component and / or combination thereof.
[0025] The embodiment of the present application provides a preparation method of an industrial X-ray film, which comprises the following steps: preparing halogenated silver cubic particle emulsion, in-situ composite modification, preparing emulsion layer coating liquid, and coating and forming. The method for preparing the silver halide cubic particle emulsion comprises the following steps: adding photographic gelatin, polyvinylpyrrolidone and sodium dioctyl sulfosuccinate into deionized water, uniformly mixing, adjusting pH to 5.5 and pAg to 7.43, simultaneously adding silver nitrate solution and potassium bromide solution at a temperature of 55-60 DEG C, and stirring after the addition is completed to obtain the silver halide cubic particle emulsion. The method for in-situ composite modification comprises the following steps: adjusting pH of the silver halide cubic particle emulsion to neutral at a temperature of 55-60 DEG C, sequentially adding zinc nitrate aqueous solution and 2-methyl imidazole aqueous solution, stirring after the addition is completed, and obtaining a reaction solution by stirring at 32-35 DEG C, and performing ultrafiltration treatment on the reaction solution to obtain a modified emulsion of in-situ composite ZIF-8. The modified emulsion is used to prepare an emulsion layer coating liquid, and then the industrial X-ray film is prepared by coating and molding.
[0026] In the preparation of the industrial X-ray film, in the step of preparing the silver halide cubic particle emulsion, polyvinylpyrrolidone and sodium dioctyl sulfosuccinate are used in combination with the double injection process, and the steric hindrance effect and electrostatic stabilization effect of the composite stabilization system composed of polyvinylpyrrolidone and sodium dioctyl sulfosuccinate on the particle preparation material are used to effectively realize uniform nucleation and controllable growth of the silver halide cubic particles, so that silver halide cubic particles with uniform size are prepared, the image granularity is reduced, and the image resolution is improved.
[0027] Further, after the silver halide cubic particles are combined with the metal organic framework ZIF-8, in the subsequent exposure process, the ZIF-8 can absorb X-ray photons in advance and enrich them, and then transfer them to the silver halide cubic particles, so that the utilization rate of X-ray photons is effectively improved, and the sensitization effect is realized.
[0028] Further, after the silver halide cubic particles are compounded with the metal organic framework ZIF-8, in the low exposure area, the weak signal can be effectively captured due to the sensitization effect of ZIF-8; in the high exposure area, the excessive merging and saturation of developed silver can be effectively prevented due to the confinement effect of ZIF-8; and the chemical cross-talk between the low exposure area and the high exposure area can be effectively prevented, so that the dynamic range of the industrial X-ray film is widened.
[0029] Further, after the silver halide cubic particles are compounded with the metal organic framework ZIF-8, the harmful substances such as water vapor and oxygen in the external environment are effectively isolated from the contact with the silver halide cubic particles through the barrier effect of ZIF-8 on the silver halide cubic particles; and the pressure resistance of the silver halide cubic particles is improved, so that the long-term stability of the industrial X-ray film, especially the pressure stability and the environmental stability, is improved.
[0030] In the embodiment of the present application, preferably, in the preparation of the silver halide cubic particle emulsion, the weight ratio of deionized water, photographic gelatin, polyvinylpyrrolidone and sodium dioctyl sulfonate is 950:50-52:4.5-4.8:0.2-0.25; The total volume ratio of deionized water to the added silver nitrate solution is 1:1.1-1.2; The total volume ratio of deionized water to the added potassium bromide solution is 1:1.1-1.2.
[0031] In the embodiment of the present application, preferably, in the preparation of the silver halide cubic particle emulsion, the molecular weight of polyvinylpyrrolidone is 45000-55000; The concentration of the silver nitrate solution is 2.9-3.1 mol / L, and the concentration of the potassium bromide solution is 2.95-3.15 mol / L.
[0032] In the embodiment of the present application, further, in the preparation of the silver halide cubic particle emulsion, under the temperature condition of 55-60℃, the dropping rate of the silver nitrate solution and the potassium bromide solution is first controlled to be constant at 4-4.5 mL / min for the first time, and after the first time of dropping is completed, the temperature is kept constant and stirring is carried out; then, the initial dropping rate of the silver nitrate solution and the potassium bromide solution is controlled to be 2-2.2 mL / min, the acceleration of the dropping rate is 1.2-1.3 mL / min, and the final dropping rate is 30-32 mL / min for the second time of dropping, and after the second time of dropping is completed, the temperature is kept constant and stirring is carried out, so that the silver halide cubic particle emulsion is prepared.
[0033] In the embodiment of the present application, preferably, the first time of dropping is 5-6 min, and the temperature keeping and stirring time after the first time of dropping is completed is 15-20 min; The second time of dropping is 50-55 min, and the temperature keeping and stirring time after the second time of dropping is completed is 15-25 min.
[0034] In the preparation of the silver halide cubic particle emulsion, by controlling the concentration of the precursor, the raw material ratio, the dropping process and other process parameters in the preparation process of the silver halide cubic particle, the uniform nucleation and controllable growth process of the silver halide cubic particle are further optimized, the crystal defects of the silver halide cubic particle are reduced, and the silver halide cubic particle with uniform size is prepared, and the photosensitive performance and pressure stability of the prepared industrial X-ray film are further improved.
[0035] In the embodiment of the present application, preferably, in the in-situ composite modification, the dropping rate of the zinc nitrate aqueous solution is 1.5-2 mL / min; The dropping rate of the 2-methyl imidazole aqueous solution is 0.7-1 mL / min; The stirring time at 32-35℃ after dropping is completed is 3-4 h; The molecular weight cut-off of the ultrafiltration treatment is 50-60 KDa.
[0036] In the embodiment of the present application, preferably, in the in-situ composite modification, the concentration of the zinc nitrate aqueous solution is 0.1-0.12 mol / L; The concentration of the 2-methyl imidazole aqueous solution is 0.3-0.36 mol / L; The volume ratio of the silver halide cubic particle emulsion, the zinc nitrate hexahydrate aqueous solution and the 2-methyl imidazole aqueous solution is 100:23-25:23-25.
[0037] In the in-situ composite modification step of the embodiment of the present application, by selecting the specifications, the raw material ratio, the dropping rate and the reaction time of the zinc nitrate aqueous solution and the 2-methyl imidazole aqueous solution, the uniform composite of the silver halide cubic particle and the metal organic framework ZIF-8 is further optimized.
[0038] In the embodiment of the present application, further, the method for preparing the emulsion layer coating liquid is that the alkyl phenol polyoxyethylene ether, the carboxymethyl cellulose and the neutral silica sol are put into the modified emulsion at a temperature of 45-50℃, and after being uniformly mixed, the photographic gelatin is added to adjust the viscosity to 12-18 mpa·s, and the emulsion layer coating liquid is prepared; The weight ratio of the in-situ composite modified emulsion, the alkyl phenol polyoxyethylene ether, the carboxymethyl cellulose and the neutral silica sol is 1000:6-6.5:4-4.3:8-8.5.
[0039] In the embodiment of the present application, preferably, the silica content of the neutral silica sol is 25-30 wt%.
[0040] In the preparation of the emulsion layer coating liquid step of the embodiment of the present application, photographic gelatin, alkyl phenol polyoxyethylene ether, carboxymethyl cellulose, neutral silica sol and modified emulsion are used in cooperation to further improve the adaptability of the emulsion layer coating liquid to the microgravure coating process, improve the coating uniformity, and further optimize the mechanical properties of the emulsion layer of the industrial X-ray film and the long-term stability of the industrial X-ray film through the cooperation of the aforementioned raw materials (especially the photographic gelatin and the neutral silica sol).
[0041] In the embodiment of the present application, further, the method for coating and forming is to coat the emulsion layer coating liquid to the front and back surfaces of the PET substrate (polyethylene terephthalate substrate) by using the microgravure coating process, control the single-sided coating thickness of the emulsion layer coating liquid to be 8-10 μm, and then coat the isolation layer coating liquid and the protective layer coating liquid to the outer surface of the emulsion layer in sequence to obtain the industrial X-ray film. The isolation layer coating liquid comprises alkyl phenol polyoxyethylene ether, glutaraldehyde, deionized water and gelatin. The protective layer coating liquid comprises alkyl phenol polyoxyethylene ether, silicone oil, glutaraldehyde, deionized water and gelatin.
[0042] In the coating and forming step of the embodiment of the present application, the isolation layer coating liquid and the protective layer coating liquid composed of specific raw materials are selected to be coated to the outer surface of the emulsion layer to form the isolation layer and the protective layer, further optimize the mechanical properties of the emulsion layer of the industrial X-ray film, and further optimize the long-term stability of the industrial X-ray film.
[0043] In the embodiment of the present application, preferably, the single-sided coating amount of the isolation layer coating liquid is 0.4-0.5 g / m 2 ; The single-sided coating amount of the protective layer coating liquid is 0.8-1 g / m 2 .
[0044] In the embodiment of the present application, preferably, the isolation layer coating liquid is prepared by uniformly mixing alkyl phenol polyoxyethylene ether, glutaraldehyde and deionized water, and then adjusting the viscosity to 12-18 mpa·s by using photographic gelatin. The weight ratio of the alkyl phenol polyoxyethylene ether, the glutaraldehyde and the deionized water is 6-6.5:1.8-2.2:1000.
[0045] In the embodiment of the present application, preferably, the protective layer coating liquid is prepared by uniformly mixing alkyl phenol polyoxyethylene ether, silicone oil and glutaraldehyde, and then adjusting the viscosity to 12-18 mpa·s by using photographic gelatin. The weight ratio of the alkyl phenol polyoxyethylene ether, the silicone oil, the glutaraldehyde and the deionized water is 6-6.5:10-11:3.5-4:1000.
[0046] The industrial X-ray film prepared by the preparation method has the following layers from near to far on the upper and lower surfaces: an emulsion layer, an isolation layer, and a protective layer.
[0047] The application will be further described in connection with some specific embodiments.
[0048] Embodiment 1 The embodiment provides a preparation method of an industrial X-ray film. 1. Preparation of halide silver cubic particle emulsion Deionized water is introduced into a reaction kettle with stirring, the stirring is started, and the temperature is raised to 55 DEG C under stirring. After 35 min of stirring and keeping the temperature, the pH of the material is adjusted to 5.5 and the pAg of the material is adjusted to 7.43. Then, under the condition of stirring at 55 DEG C, a double injection method is used to simultaneously add a silver nitrate solution with a concentration of 2.9 mol / L and a potassium bromide solution with a concentration of 2.95 mol / L. First, the dropping rate of the silver nitrate solution and the potassium bromide solution is controlled to be constant at 4 mL / min, the first dropping is stopped after 6 min, and the temperature is kept for 20 min. Then, the initial dropping rate of the silver nitrate solution and the potassium bromide solution is controlled to be 2 mL / min, the acceleration of the dropping rate is 1.2 mL / min, and the final dropping rate is 30 mL / min, the second dropping is stopped after 55 min, and the temperature is kept for 25 min. Thus, a halide silver cubic particle emulsion with an equivalent circle diameter of 0.26 μm and a size variation coefficient of 7.3% is prepared.
[0049] The weight ratio of the deionized water, the photographic gelatin, the polyvinylpyrrolidone, and the sodium dioctyl sulfosuccinate is 950:50:4.5:0.2.
[0050] The total volume ratio of the deionized water to the added silver nitrate solution is 1:1.1.
[0051] The total volume ratio of the deionized water to the added potassium bromide solution is 1:1.1.
[0052] 2. In-situ composite modification Under the temperature condition of 55℃, the pH of the silver halide cubic particle emulsion is adjusted to neutral, then the aqueous solution of zinc nitrate hexahydrate with a concentration of 0.1 mol / L is added dropwise at a rate of 1.5 mL / min under stirring, after the dropwise addition is completed, the stirring is continued for 15 min; then the aqueous solution of 2-methylimidazole with a concentration of 0.3 mol / L is added dropwise at a rate of 0.7 mL / min, after the dropwise addition is completed, the temperature is naturally lowered to 32℃, after the stirring is continued for 3 h, a reaction solution is obtained; then the reaction solution is subjected to ultrafiltration treatment, the molecular weight cut-off of the ultrafiltration is controlled to be 50 KDa, and the ultrafiltration is performed to 65% of the original volume of the reaction solution, thereby a modified emulsion of in-situ composite ZIF-8 is prepared.
[0053] The volume ratio of the silver halide cubic particle emulsion, the aqueous solution of zinc nitrate hexahydrate, and the aqueous solution of 2-methylimidazole is 100:23:23.
[0054] 3. Preparation of emulsion layer coating liquid Under the condition of 45℃ water bath heating, the alkylphenol polyoxyethylene ether, carboxymethyl cellulose, and neutral silica sol (silicon dioxide content 25 wt%) are added into the modified emulsion, after the stirring is continued for 20 min, the pre-swollen photographic gelatin is added to adjust the viscosity to 16 mpa·s, thereby the emulsion layer coating liquid is prepared.
[0055] The weight ratio of the in-situ composite modified emulsion, the alkylphenol polyoxyethylene ether, the carboxymethyl cellulose, and the neutral silica sol is 1000:6:4:8.
[0056] 4. Coating and forming The micro-gravure coating process is adopted to coat the emulsion layer coating liquid to the front and back surfaces of the PET substrate to form the emulsion layer, and the coating thickness is controlled to be 10 μm; then the isolation layer coating liquid and the protective layer coating liquid are coated to the outer surface of the emulsion layer in sequence to form the isolation layer and the protective layer in sequence, thereby the industrial X-ray film is prepared.
[0057] The isolation layer coating liquid is prepared by adding the alkylphenol polyoxyethylene ether, the glutaraldehyde, and the deionized water into the deionized water under the temperature condition of 40℃ according to the weight ratio of 6:1.8:1000, and after the stirring is continued until they are uniformly mixed, the pre-swollen photographic gelatin is added to adjust the viscosity to 16 mpa·s. In the coating and forming, the single-side coating amount of the isolation layer coating liquid is controlled to be 0.5 g / m 2 .
[0058] The protective layer coating liquid is prepared by adding alkyl phenol polyoxyethylene ether, silicon oil and glutaraldehyde into deionized water in a weight ratio of 6:10:3.5:1000 at a temperature of 40℃, stirring uniformly, and then adding pre-swollen photographic gelatin to adjust the viscosity to 16 mpa·s to obtain the protective layer coating liquid. The single-side coating amount of the protective layer coating liquid is controlled to be 0.9 g / m 2 .
[0059] The embodiment also provides an industrial X-ray film prepared by the preparation method.
[0060] Embodiment 2 The embodiment provides a preparation method of an industrial X-ray film. 1. Preparation of silver halide cubic particle emulsion The deionized water is introduced into the reaction kettle with stirring, the stirring is started, and the temperature is raised to 58℃, and then the photographic gelatin, polyvinylpyrrolidone (molecular weight 50000) and sodium dioctyl sulfosuccinate are introduced, the pH of the material is adjusted to 5.5 and the pAg of the material is adjusted to 7.43 after 35 min of stirring and temperature maintaining, and then the double injection method is used to simultaneously add the silver nitrate solution with a concentration of 3 mol / L and the potassium bromide solution with a concentration of 3.05 mol / L at 58℃ under stirring. First, the dropping rate of the silver nitrate solution and the potassium bromide solution is controlled to be constant at 4.2 mL / min, the first dropping is stopped after 5.5 min, and the stirring is maintained for 18 min; then, the initial dropping rate of the silver nitrate solution and the potassium bromide solution is controlled to be 2.1 mL / min, the acceleration of the dropping rate is 1.2 mL / min, and the final dropping rate is 31 mL / min, the second dropping is stopped after 53 min, and the stirring is maintained for 20 min, thereby obtaining the silver halide cubic particle emulsion with an equivalent circle diameter of 0.27 μm and a size variation coefficient of 7.1%.
[0061] The weight ratio of the deionized water, the photographic gelatin, the polyvinylpyrrolidone and the sodium dioctyl sulfosuccinate is 950:51:4.7:0.23.
[0062] The total volume ratio of the deionized water to the added silver nitrate solution is 1:1.1.
[0063] The total volume ratio of the deionized water to the added potassium bromide solution is 1:1.1.
[0064] 2. In-situ composite modification The pH of the silver halide cubic particle emulsion is adjusted to neutral at a temperature of 58°C, then a 0.11 mol / L aqueous solution of zinc nitrate hexahydrate is added dropwise at a rate of 1.7 mL / min under stirring, and after the dropwise addition is completed, the temperature is maintained for 20 min; then a 0.33 mol / L aqueous solution of 2-methylimidazole is added dropwise at a rate of 0.8 mL / min, and after the dropwise addition is completed, the temperature is naturally lowered to 33°C, and the temperature is maintained for 3.5 h to obtain a reaction solution; then the reaction solution is subjected to ultrafiltration treatment, the molecular weight cut-off of the ultrafiltration is controlled to be 50 KDa, and the ultrafiltration is performed to 65% of the original volume of the reaction solution to prepare a modified emulsion of in-situ composite ZIF-8.
[0065] The volume ratio of the silver halide cubic particle emulsion, the aqueous solution of zinc nitrate hexahydrate, and the aqueous solution of 2-methylimidazole is 100:24:24.
[0066] 3. Preparation of emulsion layer coating liquid Under the condition of 48°C water bath heating, the alkylphenol polyoxyethylene ether, the carboxymethyl cellulose, and the neutral silica sol (silicon dioxide content 25 wt%) are added into the modified emulsion, and after stirring for 25 min, the pre-swollen photographic gelatin is added to adjust the viscosity to 16 mpa·s to prepare the emulsion layer coating liquid.
[0067] The weight ratio of the in-situ composite modified emulsion, the alkylphenol polyoxyethylene ether, the carboxymethyl cellulose, and the neutral silica sol is 1000:6.3:4.1:8.2.
[0068] 4. Coating and forming The micro-gravure coating process is used to coat the emulsion layer coating liquid to the front and back surfaces of the PET substrate to form an emulsion layer, and the coating thickness is controlled to be 10 μm; then the isolation layer coating liquid and the protective layer coating liquid are coated in sequence on the outer surface of the emulsion layer to form an isolation layer and a protective layer in sequence to prepare an industrial X-ray film.
[0069] The isolation layer coating liquid is prepared by adding the alkylphenol polyoxyethylene ether and the glutaraldehyde into the deionized water in a weight ratio of 6.3:2:1000 under the condition of 42°C temperature, stirring uniformly, and then adding the pre-swollen photographic gelatin to adjust the viscosity to 16 mpa·s. In the coating and forming, the single-sided coating amount of the isolation layer coating liquid is controlled to be 0.5 g / m 2 .
[0070] The protective layer coating liquid is prepared by the following steps: introducing deionized water into a stirred reaction kettle, starting stirring, and stirring to raise the temperature to 42℃; then, adding alkyl phenol polyoxyethylene ether, silicon oil, and glutaraldehyde into the deionized water, stirring to make them uniform, and then adding pre-swollen photographic gelatin to adjust the viscosity to 16 mpa·s, thereby obtaining the protective layer coating liquid. In the coating forming process, the single-side coating amount of the protective layer coating liquid is controlled to be 0.9 g / m 2 .
[0071] The embodiment also provides an industrial X-ray film prepared by the preparation method.
[0072] Embodiment 3 The embodiment provides a preparation method of an industrial X-ray film. 1. Preparation of silver halide cubic particle emulsion The deionized water is introduced into a stirred reaction kettle, stirring is started, and the temperature is raised to 60℃. Then, the photographic gelatin, polyvinylpyrrolidone (molecular weight 50000), and sodium dioctyl sulfosuccinate are added, and after 40 min of stirring and keeping the temperature, the pH of the material is adjusted to 5.5 and the pAg of the material is adjusted to 7.43. Then, under the condition of stirring at 60℃, the double injection method is adopted to simultaneously add the silver nitrate solution with a concentration of 3.1 mol / L and the potassium bromide solution with a concentration of 3.15 mol / L. First, the dropping rate of the silver nitrate solution and the potassium bromide solution is controlled to be constant at 4.5 mL / min, the first dropping is stopped after 5 min, and the temperature is kept for 15 min. Then, the initial dropping rate of the silver nitrate solution and the potassium bromide solution is controlled to be 2.2 mL / min, the acceleration of the dropping rate is 1.3 mL / min, and the final dropping rate is 32 mL / min, the second dropping is stopped after 50 min, and the temperature is kept for 25 min, thereby obtaining the silver halide cubic particle emulsion with an equivalent circle diameter of 0.30 μm and a size variation coefficient of 7.6%.
[0073] The weight ratio of the deionized water, the photographic gelatin, the polyvinylpyrrolidone, and the sodium dioctyl sulfosuccinate is 950:52:4.8:0.25.
[0074] The total volume ratio of the deionized water to the added silver nitrate solution is 1:1.2.
[0075] The total volume ratio of the deionized water to the added potassium bromide solution is 1:1.2.
[0076] 2. In-situ composite modification Under the temperature condition of 60℃, the pH of the silver halide cubic particle emulsion is adjusted to neutral, then the aqueous solution of zinc nitrate hexahydrate with a concentration of 0.12 mol / L is added dropwise at a rate of 2 mL / min under stirring, after the dropwise addition is completed, the stirring is continued for 30 min; then the aqueous solution of 2-methylimidazole with a concentration of 0.36 mol / L is added dropwise at a rate of 1 mL / min, after the dropwise addition is completed, the temperature is naturally lowered to 35℃, and the stirring is continued for 4 h to obtain a reaction solution; then the reaction solution is subjected to ultrafiltration treatment, the molecular weight cut-off of the ultrafiltration is controlled to be 50 KDa, and the ultrafiltration is performed to 65% of the original volume of the reaction solution to prepare a modified emulsion of in-situ composite ZIF-8.
[0077] The volume ratio of the silver halide cubic particle emulsion, the aqueous solution of zinc nitrate hexahydrate, and the aqueous solution of 2-methylimidazole is 100:25:25.
[0078] 3. Preparation of emulsion layer coating liquid Under the condition of 50℃ water bath heating, the alkylphenol polyoxyethylene ether, carboxymethyl cellulose, and neutral silica sol (silicon dioxide content 25 wt%) are added into the modified emulsion, after stirring for 30 min, the pre-swollen photographic gelatin is added to adjust the viscosity to 16 mpa·s to prepare the emulsion layer coating liquid.
[0079] The weight ratio of the in-situ composite modified emulsion, the alkylphenol polyoxyethylene ether, the carboxymethyl cellulose, and the neutral silica sol is 1000:6.5:4.3:8.5.
[0080] 4. Coating and forming The micro-gravure coating process is used to coat the emulsion layer coating liquid to the front and back surfaces of the PET substrate to form an emulsion layer, and the coating thickness is controlled to be 10 μm; then the isolation layer coating liquid and the protective layer coating liquid are coated in sequence on the outer surface of the emulsion layer to form an isolation layer and a protective layer in sequence to prepare an industrial X-ray film.
[0081] The isolation layer coating liquid is prepared by adding the alkylphenol polyoxyethylene ether, glutaraldehyde, and deionized water into the deionized water under the temperature condition of 45℃ according to the weight ratio of 6.5:2.2:1000, stirring uniformly, and then adding the pre-swollen photographic gelatin to adjust the viscosity to 16 mpa·s. In the coating and forming, the single-sided coating amount of the isolation layer coating liquid is controlled to be 0.5 g / m 2 .
[0082] The protective layer coating liquid is prepared by adding alkyl phenol polyoxyethylene ether, silicon oil and glutaraldehyde into deionized water at a weight ratio of 6.5:11:4:1000 at 45℃, stirring uniformly, and then adding pre-swollen photographic gelatin to adjust the viscosity to 16 mpa·s to obtain the protective layer coating liquid. The single-side coating amount of the protective layer coating liquid is controlled to be 0.9 g / m2 in the coating forming process. 2 .
[0083] The embodiment also provides an industrial X-ray film prepared by the preparation method.
[0084] Comparative Example 1 For comparison, the technical scheme of Example 2 is used in Comparative Example 1, which is different in that: 1) in the preparation of the silver halide cubic particle emulsion, polyvinylpyrrolidone (molecular weight 50000) and sodium dioctyl sulfosuccinate are omitted; 2) in the preparation of the emulsion layer coating liquid step, alkyl phenol polyoxyethylene ether and neutral silicon sol (silicon dioxide content 25wt%) are omitted.
[0085] In the preparation of the silver halide cubic particle emulsion step of Comparative Example 1, the equivalent circle diameter of the prepared silver halide cubic particles is 0.35μm, and the size variation coefficient is 9.9%.
[0086] Comparative Example 2 For comparison, the technical scheme of Example 2 is used in Comparative Example 2, which is different in that: the in-situ composite modification step is omitted, and the silver halide cubic particle emulsion prepared in the previous step is directly used in the subsequent preparation of the emulsion layer coating liquid step.
[0087] The background fog density D0, modulation transfer function MTF 50 , average slope G, relative sensitivity S, exposure latitude L, maximum density D max , contrast coefficient γ, specific sensitivity S R , scratch resistance of the industrial X-ray films of Examples 1-3 and Comparative Examples 1-2 are detected, and the specific results are shown in the following table:
[0088] Further, the industrial X-ray films of Example 2 and Comparative Examples 1-2 are respectively placed in a constant temperature and humidity environment with a temperature of 55℃ and a relative humidity of 85%, and are stored for 28 days. Then, the background fog density of each industrial X-ray film is detected, and the background fog density increment ΔD0 is calculated. The calculation method of the background fog density increment ΔD0 is: the background fog density after storage-the background fog density before storage. The specific results are shown in the following table:
[0089] Furthermore, at room temperature, 50 N / cm was applied to the industrial X-ray films of Example 2 and Comparative Examples 1-2, respectively. 2 The pressure was used to conduct a pressure environment simulation test; after maintaining the aforementioned pressure for 6 hours, the background fog density of each industrial X-ray film was measured, and the background fog density increment ΔD0 was calculated. The calculation method for the background fog density increment ΔD0 is the same as the method described above. The specific results are shown in the table below:
[0090] As can be seen, in the preparation of industrial X-ray films in Examples 1-3, the preparation of silver halide cubic particle emulsion involves the use of polyvinylpyrrolidone, sodium dioctyl succinate sulfonate, and a double-injection process. The composite stabilizing system composed of polyvinylpyrrolidone and sodium dioctyl succinate effectively achieves uniform nucleation and controllable growth of silver halide cubic particles through the steric hindrance and electrostatic stabilization of the particle preparation material. This results in uniformly sized silver halide cubic particles, reducing image graininess and improving image resolution. Simultaneously, in the in-situ composite modification step, zinc nitrate aqueous solution and 2-methylimidazole aqueous solution are sequentially added to the silver halide cubic particle emulsion. Through in-situ composite, a metal-organic framework (ZIF-8) is further composited onto the silver halide cubic particles. The ZIF-8 isolates each silver halide cubic particle, inhibiting the lateral migration of silver atoms and the merging of development centers between adjacent particles during development. This improves the image edge blurring caused by silver diffusion, enhances image edge sharpness, further improves the image resolution and photosensitivity of industrial X-ray film, broadens its dynamic range, and enhances its long-term stability. The aforementioned techniques work synergistically to effectively overcome the problems of significant image graininess, lateral silver atom migration, and merging of development centers between adjacent particles. While improving image resolution, it also increases the utilization rate of X-ray photons, effectively improving photosensitivity and photosensitivity response range; and enhances the long-term stability of industrial X-ray film, especially its pressure stability and environmental stability.
[0091] It can be seen from Comparative Example 1 that polyvinylpyrrolidone and dioctyl sodium sulfosuccinate are omitted in the preparation of the silver halide cubic particle emulsion, and alkylphenol polyoxyethylene ether and neutral silica sol are omitted in the preparation of the emulsion layer coating liquid step. Due to the lack of polyvinylpyrrolidone and dioctyl sodium sulfosuccinate for effective regulation of the material system and preparation process of the silver halide cubic particles, the size and size stability of the prepared silver halide cubic particles are deteriorated to some extent; at the same time, the lack of optimization of alkylphenol polyoxyethylene ether and neutral silica sol in the emulsion layer coating liquid step reduces the adaptability of the emulsion layer coating liquid to the micro-gravure coating process, and reduces the stability of the emulsion layer itself. The comprehensive result is that the image resolution, photosensitive sensitivity, photosensitive response range, anti-scratch performance and long-term stability of the industrial X-ray film are all reduced to some extent.
[0092] It can be seen from Comparative Example 2 that the in-situ composite modification step (i.e. omitting the composite metal organic framework ZIF-8) is omitted in the preparation of the industrial X-ray film. Due to the lack of ZIF-8 for the isolation, sensitization and chemical crosstalk protection of each silver halide cubic particle, the image resolution, photosensitive sensitivity, photosensitive response range and long-term stability of the industrial X-ray film are all significantly reduced.
[0093] Unless otherwise specified, the percentages used in the present application are mass percentages.
[0094] Finally, it should be pointed out that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent replacements to some technical features. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A method of producing an industrial X-ray film, characterized by, The method comprises the following steps: preparing a silver halide cubic particle emulsion, in-situ composite modification, preparing an emulsion layer coating liquid, and coating and forming. The method for preparing the silver halide cubic particle emulsion comprises the following steps: uniformly mixing photographic gelatin, polyvinylpyrrolidone and sodium dioctyl sulfosuccinate in deionized water, adjusting the pH to 5.5 and the pAg to 7.43, and simultaneously adding silver nitrate solution and potassium bromide solution at a temperature of 55-60 DEG C, and then stirring and incubating to obtain the silver halide cubic particle emulsion. The method for in-situ composite modification comprises the following steps: adjusting the pH of the silver halide cubic particle emulsion to neutral at a temperature of 55-60 DEG C, sequentially adding zinc nitrate aqueous solution and 2-methylimidazole aqueous solution, and then stirring and incubating at 32-35 DEG C to obtain a reaction liquid, and then performing ultrafiltration treatment on the reaction liquid to obtain a modified emulsion of in-situ composite ZIF-8. The modified emulsion is used to prepare the emulsion layer coating liquid, and then coating and forming to obtain the industrial X-ray film.
2. The method of producing an industrial X-ray film according to claim 1, wherein In the method for preparing the silver halide cubic particle emulsion, the weight ratio of deionized water, photographic gelatin, polyvinylpyrrolidone and sodium dioctyl sulfosuccinate is 950:50-52:4.5-4.8:0.2-0.
25. The total volume ratio of deionized water to the added silver nitrate solution is 1:1.1-1.
2. The total volume ratio of deionized water to the added potassium bromide solution is 1:1.1-1.
2.
3. The method for preparing industrial X-ray film according to claim 1, characterized in that, In the method for preparing the silver halide cubic particle emulsion, the molecular weight of polyvinylpyrrolidone is 45000-55000. The concentration of the silver nitrate solution is 2.9-3.1 mol / L, and the concentration of the potassium bromide solution is 2.95-3.15 mol / L.
4. The method of producing an industrial X-ray film according to claim 1, wherein In the method for preparing the silver halide cubic particle emulsion, the first-time adding of the silver nitrate solution and the potassium bromide solution is performed at a constant rate of 4-4.5 mL / min at a temperature of 55-60 DEG C, and then stirring and incubating after the first-time adding is completed. Then, the second-time adding of the silver nitrate solution and the potassium bromide solution is performed at a starting rate of 2-2.2 mL / min, an acceleration rate of 1.2-1.3 mL / min and a final rate of 30-32 mL / min, and then stirring and incubating after the second-time adding is completed to obtain the silver halide cubic particle emulsion.
5. The method for preparing industrial X-ray film according to claim 4, characterized in that, The first-time adding time is 5-6 min, and the incubating time after the first-time adding is completed is 15-20 min. The second-time adding time is 50-55 min, and the incubating time after the second-time adding is completed is 15-25 min.
6. The method for preparing industrial X-ray film according to claim 1, characterized in that, In the in-situ composite modification, the adding rate of the zinc nitrate aqueous solution is 1.5-2 mL / min. The adding rate of the 2-methylimidazole aqueous solution is 0.7-1 mL / min. The incubating time at 32-35 DEG C after the adding is completed is 3-4 h. The molecular weight cut-off of the ultrafiltration treatment is 50-60 KDa.
7. The method of producing an industrial X-ray film according to claim 1, wherein In the in-situ composite modification, the concentration of the zinc nitrate aqueous solution is 0.1-0.12 mol / L. 2-methylimidazole aqueous solution has a concentration of 0.3-0.36 mol / L; The volume ratio of the silver halide cubic grain emulsion, the zinc nitrate hexahydrate aqueous solution and the 2-methylimidazole aqueous solution is 100:23-25:23-25.
8. The method for preparing industrial X-ray film according to claim 1, characterized in that, The method for preparing the emulsion layer coating liquid is as follows: alkylphenol polyoxyethylene ether, carboxymethyl cellulose and neutral silica sol are put into the modified emulsion at a temperature of 45-50 ℃, and after being uniformly mixed, photographic gelatin is added to adjust the viscosity to 12-18 mpa·s, so as to prepare the emulsion layer coating liquid; The weight ratio of the in-situ composite modified emulsion, the alkylphenol polyoxyethylene ether, the carboxymethyl cellulose and the neutral silica sol is 1000:6-6.5:4-4.3:8-8.
5.
9. The method for preparing industrial X-ray film according to claim 1, characterized in that, The method for coating and forming is as follows: the emulsion layer coating liquid is coated onto the front and back surfaces of the substrate by using a micro-gravure coating process, and the single-side coating thickness of the emulsion layer coating liquid is controlled to be 8-10 μm; then, the isolation layer coating liquid and the protective layer coating liquid are coated onto the outer surface of the emulsion layer in sequence, so as to prepare the industrial X-ray film. The isolation layer coating liquid comprises alkylphenol polyoxyethylene ether, glutaraldehyde, deionized water and gelatin. The protective layer coating liquid comprises alkylphenol polyoxyethylene ether, silicone oil, glutaraldehyde, deionized water and gelatin.
10. An industrial x-ray film, characterized by, The preparation method is prepared by using any one of claims 1-9.
Citation Information
Patent Citations
Method of making a lithographic printing plate
CN101861547A
Preparation method of nano-enzyme hydrogel sheet and application of nano-enzyme hydrogel sheet in band-aid
CN113975459A
Silver halide photographic sensitive material and its manufacture and image forming method
JP1996201956A
X-ray image forming method and treatment of silver halide photosensitive material
JP2000019666A
Recording material support, process for manufacturing the same, recording material and process for image formation
US20030198885A1
